Company's Characteristic Influencing the Success of Bank IPOs - Selamat Surbakti (Business and Entrepreneurial Review, 2007)
The background of this study is Bank requirement to make fund available for business expansion, renewall of technology, research and development. Upon company's listing in stock exchange (Jakarta Stock Exchange). Bank will have fresh founds from public (investors) as a result of stock selling to public. One of investments that most investors prefer in capital market is IPO. IPO is a moment, which the initial stock is published and offered to public. The objective of this study is to analyze company's characteristic influencing the success of Bank IPO. This study takes 21 publicly listed banks at Jakarta Stock Exchange (JSE) as the object of this study and there are 7 variables elected as the parameters of the success of IPOs. Data analysis used in this study is from prospectus and data transaction of the company that was publishd in Jakarta Stock Exchange. The result of this study conclude that there is no variables (size effect, age at the offering, IPO Activity, initial return, market level, number of risk factors, and insider ownership) that influence the success of the Bank IPOs aftermarket.